'Who can support me?': Studying teacher leadership in a Hong Kong primary school. (January 2020) - Wan, Sally Wai-Yan; Tse, Yuen-Shan; Tsang, Wing-Ki; Lee, Thomas Wing-Ki; Wong, Ylena Yan; Wan, Ada Wing-Tung; Wan, Wai-Po Eunice
Teacher leadership is one of the essential factors in curriculum implementation. Curriculum development is never an easy task for teachers. Several studies have indicated that teacher leadership has led to school improvement and fostered student achievement and engagement in learning. However, most studies have focused on examining teacher leadership in Western contexts; rarely have studies been conducted to explore how teacher leadership takes place in an 'East meets West' context. The aims of the mixed-method study are the following: (a) to investigate teachers' perceptions and experiences of teacher leadership, and (b) to explore how teachers act out teacher leadership in a peer network. This study used the case of a local primary school. Data collection methods included teacher surveys, individual interviews with teachers, and field notes from a one-day teacher shadowing. The data indicated that teachers were more oriented towards student learning, but insufficient space was available for enacting teacher leadership in terms of teacher collaboration, shared leadership and reflective practice. Thus, implications for teacher leadership development are discussed.